2018
DOI: 10.1096/fj.201700088rr
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling: demethylating H3K4me3 of type I IFNs gene by Rbp2 through interacting with Piasy for transcriptional attenuation

Abstract: Type I IFNs (IFNIs) are involved in the course of antiviral and antimicrobial activities; however, robust inductions of these can lead to host immunopathology. We have reported that the Pias (protein inhibitor of activated signal transducer and activator of transcription) family member, Piasy, possesses the ability to suppress IFNI transcriptions in mouse embryonic fibroblasts (MEFs), yet the specific molecular mechanism by which it acts remains elusive. Here, we identify that the H3K4me3 levels, one activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Cannabidiol (CBD) is a major, biologically active, phytocannabinoid that has recently become increasingly used in cytoprotection [1,2]. Since CBD does not show any psychoactive action, there are many efforts focused on the use of the anti-inflammatory and protective properties of CBD in different therapies [3,4]. To date, it has been shown that CBD can act as a reactive oxygen species (ROS) scavenger and as an antioxidant in cells under stress conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cannabidiol (CBD) is a major, biologically active, phytocannabinoid that has recently become increasingly used in cytoprotection [1,2]. Since CBD does not show any psychoactive action, there are many efforts focused on the use of the anti-inflammatory and protective properties of CBD in different therapies [3,4]. To date, it has been shown that CBD can act as a reactive oxygen species (ROS) scavenger and as an antioxidant in cells under stress conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…S5b). Similarly, KDM5B protein expression level was much lower in Pias4-/-MEF cells than in Pias4+/+ MEF cells 13 (Additional le: Fig. S5c).…”
Section: Pias4 Was the Sumo E3 Ligase For Hypoxia-induced Kdm5b Sumoylationmentioning
confidence: 86%
“…Cell culture and small molecule chemical inhibitors Nine Human GC cell lines (SGC7901, BGC823, MKN45, AGS, HGC-27, MKN28, MGC803, N87, and MFC), a human normal gastric epithelial cell line (GES-1), and HEK293T were all purchased from Cell Bank of the Typical Culture Preservation Committee, Chinese Academy of Sciences (Shanghai, China). MEF cells from Pias4+/+ and Pias4-/mice were generous gifts from Prof. Shuai Ke (University of California, Los Angeles, Los Angeles, CA, USA) 13 . SGC7901/BGC823-shNC and SGC7901/BGC823-shKDM5B cells were generated via infection of lentiviral vectors containing shRNA (shscramble and shKDM5B) and puromycin selection.…”
Section: Methodsmentioning
confidence: 99%
“…As shown, KDM5B protein level was reduced in GC cells after PIAS4 knockdown (Figures 3A,B). Similarly, the KDM5B protein level was much lower in Pias4 −/− MEF cells than that of Pias4 +/+ MEF cells (Yu et al, 2018) (Supplementary Figure S4B). Meanwhile, the half-life of KDM5B protein was shortened in GC cells after PIAS4 knockdown under hypoxia conditions (Figures 3C,D).…”
Section: Pias4 Was the Sumo E3 Ligase For Hypoxia-induced Kdm5b Sumoylationmentioning
confidence: 90%
“…Nine human GC cell lines (SGC7901, BGC823, MKN45, AGS, HGC-27, MKN28, MGC803, N87, and MFC), a normal human gastric epithelial cell line (GES-1), and HEK293T were all purchased from the Cell Bank of the Typical Culture Preservation Committee, Chinese Academy of Sciences (Shanghai, China). MEF cells from Pias4 +/+ and Pias4 −/− mice were generous gifts from Prof. Shuai Ke (University of California, Los Angeles, CA, United States) (Yu et al, 2018). SGC7901/ BGC823-shNC and SGC7901/BGC823-shKDM5B cells were generated via the infection of lentiviral vectors containing shRNA (shscramble and shKDM5B) and puromycin selection.…”
Section: Cell Culture and Small-molecule Chemical Inhibitorsmentioning
confidence: 99%